2020
DOI: 10.3390/life10020016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Resistance in Gram-Negative Urinary Isolates Using Existing and Novel Indicators of Clinical Relevance: A 10-Year Data Analysis

Abstract: Classical resistance classifications (multidrug resistance [MDR], extensive drug resistance [XDR], pan-drug resistance [PDR]) are very useful for epidemiological purposes, however, they may not correlate well with clinical outcomes, therefore, several novel classification criteria (e.g., usual drug resistance [UDR], difficult-to-treat resistance [DTR]) were introduced for Gram-negative bacteria in recent years. Microbiological and resistance data was collected for urinary tract infections (UTIs) retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 54 publications
2
73
1
3
Order By: Relevance
“…The link between colonization and infection by K. pneumoniae in hospitalized patients has been demonstrated, with robust evidence that their own microbiota is the main source of the infective strains [35,36]. Thus, potentially more virulent K. pneumoniae strains may take advantage of critical conditions, becoming responsible for nosocomial infections [37].…”
Section: Discussionmentioning
confidence: 99%
“…The link between colonization and infection by K. pneumoniae in hospitalized patients has been demonstrated, with robust evidence that their own microbiota is the main source of the infective strains [35,36]. Thus, potentially more virulent K. pneumoniae strains may take advantage of critical conditions, becoming responsible for nosocomial infections [37].…”
Section: Discussionmentioning
confidence: 99%
“…6,11,15,16 Novel resistance classifications for Gram-negative bacteria suggested that an extended-spectrum β-lactamase (ESBL)-producing, carbapenem-resistant and fluoroquinolone-resistant isolate was considered as difficultto-treat resistance (DTR). 17 Infections, especially bloodstream infections caused by CRKP can cause significantly high mortality, for the reason that it expresses multidrug resistance phenotypes so that antimicrobial treatments appear to be quite intractable. In our study, the 28-day mortality of CRKP BSI among patients with hematologic malignancies reached 77.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their transmissibility, ESBLs are considered a serious public health/infection control issue, especially because these enzymes are encoded on larger-sized plasmids [18,30,34]. As several resistancedeterminants are often present in bacteria simultaneously, in addition to b-lactams, other antibiotic-groups may be affected, rapidly resulting in MDR, or even XDR strains, with severely limited therapeutic options left [26,35]. These isolates have been associated with increased morbidity and mortality, particularly in ICUs and in severely immunocompromised patients [36].…”
Section: Resistotype Ciprofloxacinmentioning
confidence: 99%